PRESERVING PEGON: A CASE STUDY ON KAMPUNG SANTRI TARJUMAH IN TAMBANGSARI, PATI REGENCY-CENTRAL JAVA - Lina Kushidayati; Moh. Rosyid (Al Qalam, 2019)
The manuscript is written to portray a hamlet which formed pesantren (Islamic Boarding School) in which the santri (students) consists of santri mukim (students staying in boarding school) from various regions and santri kalong (local residents) and in which there is a mosque, a boarding school, an Al-Quran educational park, a madrasah diniyah, houses of clerics (in one settlement of village), the learning system of bandongan using the Tarjumah Book with Pegon-language written by KH Ahmad Rifa'i. The action of K. Rifai against Dutch colonialism was known as the Rifaiyah movement, his resistance with the movement of writing the Book of Tarjumah which contained Tawheed, Fiqh, and Sufism written in Pegon. Pegon was a resistance form against colonial Latin writing. Until now it was continued by his santri in the village where he lived serving as the cleric of Islamic Boarding School. The location of this research is in Tambangsari Hamlet, Kedungwinong Village, Sukolilo District, Pati Regency, Central Java. The data were obtained from January to June 2019 through interviews and observation with a descriptive qualitative approach. This hamlet of rice plantation and palawija (secondary crops) has formed a specialty called the tarjumah santri village. The successor generation of K. Rifai’s student who introduced the Book of Tarjumah in Tambangsari Hamlet was K.Hannan and it is now continued by his grandson. The learning of the Tarjumah Book had formed a distinctive hamlet community, namely dukuh santri. The obedience in worship with the knowledge of Islamic religion through the tradition of learning the Salaf Tarjumah across ages and genders and with the behavior in life adhering to Islamic law has been a social reality.